2021
DOI: 10.3390/agronomy11122591
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Titanium Organic Complex on Pollination Process and Fruit Development of Apple cv. Topaz

Abstract: Optimal weather conditions are necessary for the proper course of the flowering process and high activity of pollinators, which is the most important factor affecting pollination. Because weather conditions do not always favour effective pollination and because pollinators’ activities are decreasing, the application of compound stimulating pollination and fertilization may be a good perspective for increasing yield. Titanium is considered a beneficial element for plants. Preliminary studies have indicated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…However, there was a tendency to a higher number of germinating pollen grains on the stigma of plants sprayed with TOC. Bieniasz and Konieczny [27] obtained similar results in the cultivation of apple. In the two following growing seasons, these authors sprayed an apple tree with TOC and observed more pollen grains on stigma and more pollen tubes reaching the ovary.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…However, there was a tendency to a higher number of germinating pollen grains on the stigma of plants sprayed with TOC. Bieniasz and Konieczny [27] obtained similar results in the cultivation of apple. In the two following growing seasons, these authors sprayed an apple tree with TOC and observed more pollen grains on stigma and more pollen tubes reaching the ovary.…”
Section: Discussionsupporting
confidence: 52%
“…Dyki et al [25] performed the first studies, which showed that TOC positively affected pollination and fertilization processes, seed formation and fruit development of tomato and cucumber. Research carried out by these authors was followed by Bieniasz and Konieczny [27] and Bieniasz et al [35], who also demonstrated that TOC positively affected the pollination process, seed setting and mass of individual fruit of apples and strawberries, respectively. Janas [26] and Radkowski et al [28] in solanaceous crops and timothy demonstrated a higher number of seeds and their better quality as a result of the use of TOC, but did not conduct analysis of pollen adhesion to the stigma and growth of the pollen tube.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), and blueberry (Vaccinium spp. ), resulting in increased fruit set rate and fruit yield [45][46][47]. However, further research is required to establish whether the application of titanium directly promotes crop pollination and fertilization.…”
Section: The Plant Growth Was Stimulated By Titaniummentioning
confidence: 99%